2018
DOI: 10.1128/jvi.00175-18
|View full text |Cite
|
Sign up to set email alerts
|

The Superimposed Deubiquitination Effect of OTULIN and Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) Nsp11 Promotes Multiplication of PRRSV

Abstract: Linear ubiquitination plays an important role in the regulation of the immune response by regulating nuclear factor κB (NF-κB). The linear ubiquitination-specific deubiquitinase ovarian tumor domain deubiquitinase with linear linkage specificity (OTULIN) can control the immune signaling transduction pathway by restricting the Met1-linked ubiquitination process. In our study, the porcine OTLLIN gene was cloned and deubiquitin functions were detected in a porcine reproductive and respiratory syndrome virus (PRRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…(iii) nsp11 removes the ubiquitin chains from IκBα (inhibitor of NF-κB alpha), thereby preventing the proteasomal degradation of IκBα and subsequent liberation of NF-κB ( 39 ). (iv) nsp11 recruits the OTU deubiquitinase with linear linkage specificity (OTULIN) to enhance its ability to remove the cellular protein ubiquitin associated with innate immunity, resulting in the additive effect of suppressing type I IFN production ( 40 ). However, whether nsp11 also regulates IFN signaling remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…(iii) nsp11 removes the ubiquitin chains from IκBα (inhibitor of NF-κB alpha), thereby preventing the proteasomal degradation of IκBα and subsequent liberation of NF-κB ( 39 ). (iv) nsp11 recruits the OTU deubiquitinase with linear linkage specificity (OTULIN) to enhance its ability to remove the cellular protein ubiquitin associated with innate immunity, resulting in the additive effect of suppressing type I IFN production ( 40 ). However, whether nsp11 also regulates IFN signaling remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, TRAIP has been reported to be a gene involved in innate immunity (39). Therefore, we further explored whether there is an interaction between the TRAIP and PRRSV non-structural proteins nsp1, nsp4, nsp11, each of which is a major protein involved in inhibiting the IFN-β and NF-κB promoters (41, 43, 44). We first observed that Flag-tagged TRAIP interacted with Myc-nsp1 (Supplementary Figure 1), and the interaction between TRAIP and nsp1 was confirmed by co-immunoprecipitation (Supplementary Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…Human embryonic kidney (HEK) 293T cells and HeLa cells were maintained in Dulbecco's modified Eagle's medium (DMEM, Gibco) with 10% FBS supplemented with an antibiotic-antimycotic mixture of 100 mg/ml streptomycin, 100 IU/ml penicillin and 50 U/ml amphotericin B. The cells were maintained in a humidified 5% CO 2 incubator at 37°C.The PRRSV-JXwn06 strain was used in our study and the titer was determined to be 104 PFU/ml as previously described (41).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure for confocal microscopy has been described previously (Su et al, 2018). IPEC-J2 cells were seeded on 12-well plates until the cell density was about 60%˜70%.…”
Section: Immunofluorescencementioning
confidence: 99%